Indonesian’s Mathematics Teacher Comprehension Towards Geogebra - Intan Kertiyani; Rahma Nasir; Uncok Manigor Jokkas Siahaan (FKIP Universitas Mataram, 2024)
Numerous studies have mentioned that Geogebra provides positive impacts towards mathematics lessons and suggested to integrating this software into the classroom activity. In order to prepare the teacher for Geogebra integration, study for teacher comprehension of Geogebra is required as the basic for future study. This paper aimed to capture Indonesian mathematics teacher comprehension about Geogebra. This was descriptive study using survey method. The sample was 296 junior high school mathematics teachers. The teachers were asked to fulfilled the questionnaire to obtain their comprehension towards Geogebra. The results revealed that 50% teachers were at level 1 in understanding the features of Geogebra and more than half of them has never been utilized Geogebra in their mathematics lesson and never been construct an applet Geogebra as their instructional media. Those results suggest the urgency to provide the Geogebra training for mathematics teacher in order to enhace students comprehension towards Geogebra.